2017
DOI: 10.1111/ijtd.12107
|View full text |Cite
|
Sign up to set email alerts
|

Training for creativity and innovation in small enterprises in Ethiopia

Abstract: Policy makers recognize the role of small businesses in bringing about economic growth and reducing or eliminating poverty, and training can contribute significantly to this process. The present study adds to the small firm literature by examining whether training encourages small firms to be more creative and innovative. It does so by investigating the extent of creative and innovative activities in small enterprises (SEs) that have undertaken training with support from the Ethiopian technical and vocational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There is a growing consensus that entrepreneurship training offered to microentrepreneurs enables them to acquire knowledge, skills and attitudes (KSAs) that can be applied to improve clients' enterprise growth and sustainability (Gegenfurtner et al, 2020; Prediger & Gut, 2014). It is often argued that effective entrepreneurship training contributes considerably toward eliminating poverty by transforming the poor into successful microentrepreneurs (Abeysekera et al, 2017; Mihret Dessie & Shumetie Ademe, 2017). However, training initiatives face criticism of failure to enhance entrepreneurship in developing economies which exhibit enormous skill gaps (Awais Bhatti et al, 2013; Oware, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing consensus that entrepreneurship training offered to microentrepreneurs enables them to acquire knowledge, skills and attitudes (KSAs) that can be applied to improve clients' enterprise growth and sustainability (Gegenfurtner et al, 2020; Prediger & Gut, 2014). It is often argued that effective entrepreneurship training contributes considerably toward eliminating poverty by transforming the poor into successful microentrepreneurs (Abeysekera et al, 2017; Mihret Dessie & Shumetie Ademe, 2017). However, training initiatives face criticism of failure to enhance entrepreneurship in developing economies which exhibit enormous skill gaps (Awais Bhatti et al, 2013; Oware, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, training initiatives face criticism of failure to enhance entrepreneurship in developing economies which exhibit enormous skill gaps (Awais Bhatti et al, 2013; Oware, 2020). These gaps cause the majority of micro, small and medium enterprises (MSMEs) to be plagued with a lack of creativity and innovation (Mihret Dessie & Shumetie Ademe, 2017) and a low graduation rate to the next level (Henrekson & Johansson, 2010). Consequently, several scholars (e.g., Brown et al, 2015; Lensink et al, 2018) question the compatibility of entrepreneurship training with trainees' specific needs and characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, external SC is also called bridging social (16) bonding social capital. (20) It is conceived as a network of external actors made up of indispensable agents for the company, for example, clients and suppliers, and participants who offer similar products and services, that is, competitors and social actors, such as government institutions. (17) External SC involves being clear about the achievements and advantages of having relationships with external stakeholders, systematically investing time and resources to strengthen trust to maintain long-term relationships and generate reciprocal benefits (21) Empirical studies on external SC have reported important contributions of this asset for innovation in organizations, among which we can mention the significant positive effect of external SC on entrepreneurs' generation of business ideas.…”
Section: External Rsc In Organizations and Innovationmentioning
confidence: 99%
“…For example, Pajo, Coetzer, and Guenole (2010) found that entrepreneurial firms that provide their employees with training and development opportunities reduce their turnover intentions. Dessie and Ademe (2017) argue that introducing training practices enhances creativity and innovative behavior among employees in entrepreneurial firms. Moreover, Bryson and White (2019) suggest that formal HRM practices first disturb the intrinsic motivation of employees, but the adoption of a particular type of formal HRM practices, namely high-performance work practices (i.e., HRM practices aimed at developing employee skills and abilities and creating opportunities for employees to contribute (Jiang & Liu, 2015;Posthuma, Campion, Masimova, & Campion, 2013)), can restore motivation among employees.…”
Section: Individual-level Outcomes Of Hrmmentioning
confidence: 99%
“…Saridakis, Muñoz Torres, and Johnstone (2013) Job satisfaction moderates the positive effect between formal HRM practices and affective commitment. Qualitative Dessie and Ademe (2017) Training aimed at creative thinking and motivation is positively linked to innovative behavior of employees. Jebali and Meschitti (2020) Employees are more likely to exhibit more innovative behavior if they actively engage in formally structured training practices.…”
Section: Lai Et Al (2017)mentioning
confidence: 99%